Invited to Witness Solidarity Tourism across Occupied Palestine - Lynn Kelly, Jennifer (Duke University Press, 2022)
Jennifer Lynn Kelly explores the significance of contemporary solidarity tourism in Palestine/Israel, showing how such tourism functions both as political strategy and emergent industry.